Phenotyping Deficit Moisture Stress Tolerance in Tomato Using Image Derived Digital Features - Laxman, R. H.; Hemamalini, P.; Namratha, M. R.; Bhatt, R. M.; Sadashiva, A. T. (International Journal of Bio-resource and Stress Management, 2022)
Evaluation of tomato genotypes for the response to water stress using digital features assists in high-throughput phenotyping. A study was conducted on imaging tomato genotypes maintained at field capacity and water deficit stress at flowering stage during 2016 at the plant phenomics facility, ICAR-Indian Institute of Horticultural Research, Bengaluru, Karnataka, India. Image derived digital features were obtained through image analysis. Physiological parameters, relative water content, water potential and quantum efficiency of PSII were measured at field capacity and water deficit stress conditions. Study established the relationship between physiological functionality and digital features of tomato plants. Transition of plants from field capacity to water stress caused reduction in digital biomass and canopy top area (CTA) among nine tomato genotypes. Deficit moisture stress resulted in lower relative water content, water potential and quantum efficiency of PSII. We observed an apparent relationship between physiological functionality and digital features, convexhull area and compactness. Two genotypes, IIHR 2843 and IIHR 2195 displayed contrasting response under 100% and 50% FC moisture regimes. At 50% FC, the genotypes IIHR 2843 and IIHR 2195 showed lower and higher water use efficiency, respectively. Genotype IIHR 2195 not only continued to sustain biomass production under deficit moisture stress but showed lower water consumption and higher water use efficiency compared to IIHR 2843. Apparent relationship established between physiological functionality and the digital features in this study clearly indicated that the digital features could be employed to capture the response of tomato genotypes to water deficit stress.